Consequences of COVID-19 Lockdown Restrictions on Children Physical Activity-A Slovenian Study - Jurij Planinšec; Črtomir Matejek; Saša Pišot; Rado Pišot; Boštjan Šimunič (Frontiers Media S.A., 2022)
During the COVID-19 pandemic, countries took several restrictions to contain the spread of coronavirus. In the second wave of the COVID-19 pandemic, primary schools in Slovenia were closed for a period long time (from October 19th 2020 until January 18th 2021 when they were partially reopened for 6-9 year olds until February 15th 2021 when they were reopened for all children) and organized sport activities for children and adolescents under the age of 15 was not allowed during this period. The aim of the study was to examine how these restrictions were reflected in the amount of different forms of physical activity (PA) of 6-12-year old children (N = 3,936). Data were collected using an online questionnaire (International Physical Activity Questionnaire Short Form) comparing different forms of PA before (BEFORE) and during (DURING) remote schooling. The results show that there has been a decline in children's PA DURING, specifically, only 4.3% of children had their physical education ≥ 45 min (or 77.7% ≤ 30 min), as is the usual duration in Slovenia. There was also a remarkable decline in extracurricular sports activities (p < 0.001), which BEFORE had been participated by 72.2% of children, while DURING remote schooling, as many as 83.5% of children did not participate these activities. 69.7% of children participated in organized sports in clubs at least once a week, while DURING remote schooling, as many as 88.1% (p < 0.001) did not participate in such form of activities. Furthermore, the time spent exercising in moderate to vigorous PA also decreased (BEFORE 8.2% vs. DURING 24.9%; p < 0.001). We found that during lockdown there has been an alarming decrease in the frequency and duration of organized PA at school and at sports clubs. These findings are a good starting point for designing (developing) an effective strategy for promoting health-enhancing PA of children in the event of a future lockdown or similar situations. The strategy should focus on the appropriate implementation of PA curriculum and motivate young people to participate regularly in extracurricular organized and non-organized activities.